Desert journeys: from exploration to covert operations. Issue 3 (2nd February 2015) - Forsyth, Isla
Abstract : This paper explores the entangled relationship between geographical knowledge and covert warfare through a study of soldier and desert explorer Ralph Bagnold. On Italy's declaration of war in 1940 the British military became engaged in a process of transforming the desert plains of the Middle East into an unnerving, obscure battlefield. General Wavell, Commander in Chief, ensured he drew upon those with a grounded understanding of this shifting terrain. Bagnold drew Wavell's attention because he had previously conducted pioneering aeolian research (later published as the seminal The physics of blown sand and desert dunes 1941, Methuen), as well as having developed desert‐based technologies for exploration. Due to Bagnold's intimate knowledge of the desert he was perfectly positioned to be charged with a small, specially equipped force that could wreak havoc behind enemy lines; a covert unit known as the Long Range Desert Group (LRDG). This study of Bagnold's desert exploration and the emergence of the LRDG in WWII will uncover how geographical knowledge became engrained within the prosecution of desert warfare. The paper explores the ways in which the particularities of the desert shaped technologies of mobilities and covert methods of conflict and how the geographies of the desert have been informed through military‐inflected exploration combined with technological innovation.